Mode specificity in the OH + CHD 3 reaction: Reduced-dimensional quantum and quasi-classical studies on an ab initio based full-dimensional potential energy surface - Yang, Minghui (2017)
An initial state selected time-dependent wave packet method is applied to study the dynamics of the OH + CHD3 reaction with a six-dimensional model on a newly developed full-dimensional ab initio potential energy surface (PES). This quantum dynamical (QD) study is complemented by full-dimensional quasi-classical trajectory (QCT) calculations on the same PES. The QD results indicate that both translational energy and the excitation of the CH stretching mode significantly promote the reaction while the excitation of the umbrella mode has a negligible effect on the reactivity. For this early barrier reaction, interestingly, the CH stretching mode is more effective than translational energy in promoting the reaction except at very low collision energies. These QD observations are supported by QCT results. The higher efficacy of the CH stretching model in promoting this early barrier reaction is inconsistent with the prediction of the naively extended Polanyi’s rules, but can be rationalized by the recently proposed sudden vector projection model.